Bioenergy and agriculture: Promises and challenges: Bioenergy and the poor - Karekezi, Stephen; Kithyoma, Waeni (International Food Policy Research Institute, 2006)
Biomass is a primary source of energy for close to 2.4 billion people in developing countries. Easily available to many of the world’s poor, biomass provides vital and affordable energy for cooking and space heating. Although widespread use of traditional and inefficient biomass energy in poor countries has been linked to indoor air pollution as well as to land degradation and attendant soil erosion, biomass-based industries are a significant source of jobs and income in poor rural areas with few other opportunities The share of biomass energy in total energy consumption varies across developing countries, but generally the poorer the country, the greater its reliance on traditional biomass resources (see figure). Biomass has considerable potential to become more important in total energy consumption, and this growth could have significant impacts, both positive and negative, on agriculture and the poor. This brief delineates two broad categories for bioenergy development—the exploitation of existing agricultural wastes and the establishment of energy plantations—and suggests high-priority steps for developing bioenergy in ways that benefit the poor.